INTEGRATION OF SUSTAINABLE DEVELOPMENT PRINCIPLES INTO THE MARKETING STRATEGIES OF IT-COMPANIES - HONCHAR, Mykhailo; ZELENEVYCH, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is dedicated to analyzing current trends and innovations in the field of sustainable marketing for IT companies, particularly in the context of ecological and social challenges arising amidst globalization, digital changes, and intense market competition. The article examines the main strategies for integrating sustainable practices into marketing processes, including the use of digital technologies to ensure transparency and ethically responsible business practices. The authors emphasize the importance of corporate social responsibility, as well as the development of "green" marketing strategies that involve resource usage with minimal environmental impact and support social initiatives. The role of combating "greenwashing," which has become an important aspect of modern marketing practice, is also highlighted. Successful case studies of leading IT companies that implement innovative solutions for integrating sustainability principles into marketing strategies, boosting customer loyalty, and strengthening brand reputation at the international level are separately examined. It is determined that organizations that actively adopt sustainable marketing practices can not only improve their economic standing but also contribute to the development of social and ecological standards in the market. The article also outlines key challenges and barriers to sustainable development in marketing, such as the insufficient awareness of companies regarding the importance of ecological and social aspects of marketing, as well as difficulties in integrating cutting-edge technologies and standards into corporate strategic management. Recommendations for IT companies on integrating sustainability principles into their strategies are provided, particularly through the formation of an ethical brand, supporting transparency in communications, and creating environmentally friendly products and services. The article explores the prospects for the development of the sustainable marketing industry in the context of rapidly adapting to changing economic realities, taking into account the constant development of technologies, social demands for professional business responsibility, and consumer desires for more conscious consumption. Key aspects for the future development of this industry include innovations in creating ecological products, the development of partnerships between businesses and social initiatives, and companies' ability to adapt to environmental standards.
Keywords: IT-companies; marketing strategies; corporate social responsibility; sustainable development; competitiveness